PENGEMBANGAN SISTEM INFORMASI PERSEDIAAN OBAT MENGGUNAKAN MODEL FIRST IN FIRST OUT DI APOTEK AL MA’SOEM BANDUNG - Encep Supriatna (Masoem University, 2018)
Al Ma'soem pharmacy headquartered at Jl. Horse Race No. 46 Arcamanik Bandung, currently has 17 branches of pharmacies spread across several cities and regencies in West Java, including Bandung, Sumedang, Majalengka, Garut, and Cianjur. Good governance system makes Apotek Al Ma'soem grow and develop rapidly in several cities and districts in West Java. In the sales system has been supported with adequate information technology, so that drug sales services can be done effectively. The method used to assess the supply of drugs in pharmacies is to use the last price method. The impact of the application of the method of inventory value becomes unreal because the price used to assess the inventory is not the actual cost, but the last price entered. Likewise, the gross profit generated by the system becomes unreal because the gross profit generated by the system is not the difference between the selling price and the acquisition price, increment the difference between the selling price and the last price. This will certainly make it difficult for the financial section to calculate and make adjusting entries because there will be differences between cash flow reports with inventory reports, purchases and sales generated by the system.The purpose of this research is to develop inventory system using FIFO (First In First Out) model, which is to assess inventory according to its cost. The goal is to generate inventory reports and real gross sales income, making it easier for the financial section in preparing financial statements and minimize the occurrence of financial fraud. The system development method used is a prototype with the stages of collecting all the needs, building prototyping, prototyping evaluation, encoding the system, testing the system, evaluating the system, and using the system.The development of this system can result in reports of drug supplies and real gross earnings so as to minimize the occurrence of financial fraud resulting from the difference in nominal value of money with the value contained in the report, as well as facilitate and streamline the work of the financial section in loading financial statements.